Effect of graded competition on student opportunities for participation and success rates during a season of Sport Education. (4th May 2017) - Hastie, Peter A.; Ward, Jeffrey K.; Brock, Sheri J.
ABSTRACT: Background : A guiding principle of Sport Education is that all students get equal opportunity to play, which is expedited through the use of small-sided contests. One element included within the philosophy of Sport Education is that of 'graded competition.' In graded competition, leagues are arranged that match students of similar skill level against one another, and in some cases, even the game forms are different across the competition levels. To date, there are no studies that have examined the utility of graded competition as promoting either student engagement or learning. Purpose : The purpose of this study was to test the hypothesis that using graded competition would increase opportunities for game involvement and success rates of both higher and lower skill level students. Participants and setting : The participants in this study were 106 fourth-grade students (51 boys and 55 girls, aged 10–11) from two physical education classes within an elementary school in the southeastern United States. The content was an 18-lesson season of mini-handball taught following the principles of Sport Education. While the overall season format for both classes was the same, the composition of teams varied between the two. In the first class, all teams were heterogeneous with a mix of higher and lower skilled players. These students were able to divide into their sub-teams in any combination they wished. In the second class, two homogeneous leagues were formed; one consisting of teams with all higher skilled students and the other with teams of all lower skilled students. There was no inter-league play. Rather, there were two parallel competitions and two championships. Methods : Digital video records were made of 76 games played during the seasons. Each time a player (a) made contact with the ball (a pass, catch, or interception), (b) was the target of a pass but did not receive it (overthrow or interception), or (c) was involved with a shot on goal (as shooter or goalkeeper), that activity was recorded. A 2 (skill: high/low) × 2 (sex) × 3 (grouping: all low/all high/mixed) full factorial mixed analysis of variance was conducted on the following dependent variables: (a) percent success, (b) ball engagement rate, and (c) efficiency, with the game being the unit of analysis. Findings : The key finding from this study was that in terms of success rates, engagement rates and playing efficiency, lower skilled students seemed to be at a disadvantage when they participated alongside higher skilled classmates. While less severe, there were also decrements in higher skilled student success rates and efficiency in these mixed-skill conditions. By consequence, while higher skilled boys could thrive in either homogenous or mixed level competitions, many girls and all students with lower skill levels benefitted from playing against students of similar skill levels. Conclusions : The grouping of students in terms of skill level has implications for their in-game behaviors, for the extent to which they can develop improved game performance, and potentially for their motivation to persist during play.